Real time flood detection & monitoring system with wireless network sensors - Nur Ainina Asyra, Abdul Kadir (2016)
Real Time Water Level Monitoring System with Wireless Network Sensors for Flood was developed to help population on flood risk area especially for those who live by the riverbank to make early preparation before the flood come. In this system, the sensor will detect distance between the sensor placement and the water surface. The measurement will be collected for every hour. Water monitoring system will receive data from sensors. Data collected will be stored into the database. The data will be used to analyze the pattern of water rising. This analysis will help in predict the flood.